Do physician communication skills influence screening mammography utilization? - Meguerditchian Ari-Nareg; Dauphinee Dale; Girard Nadyne; Eguale Tewodros; Riedel Kristen; Jacques André; Meterissian Sarkis; Buckeridge David L; Abrahamowicz Michal; Tamblyn Robyn (BMC, 2012)
Abstract Background The quality of physician communication skills influences health-related decisions, including use of cancer screening tests. We assessed whether patient-physician communication examination scores in a national, standardized clinical skills examination predicted future use of screening mammography (SM). Methods Cohort study of 413 physicians taking the Medical Council of Canada clinical skills examination between 1993 and 1996, with follow up until 2006. Administrative claims for SM performed within 12 months of a comprehensive health maintenance visit for women 50-69 years old were reviewed. Multivariable regression was used to estimate the relationship between physician communication skills exam score and patients' SM use while controlling for other factors. Results Overall, 33.8 % of 96,708 eligible women who visited study physicians between 1993 and 2006 had an SM in the 12 months following an index visit. Patient-related factors associated with increased SM use included higher income, non-urban residence, low Charlson co-morbidity index, prior benign breast biopsy and an interval >12 months since the previous mammogram. Physician-related factors associated with increased use of SM included female sex, surgical specialty, and higher communication skills score. After adjusting for physician and patient-related factors, the odds of SM increased by 24 % for 2SD increase in communication score (OR: 1.24, 95 % CI: 1.11 - 1.38). This impact was even greater in urban areas (OR 1.30, 95 % CI: 1.16, 1.46) and did not vary with practice experience (interaction p-value 0.74). Conclusion Physicians with better communication skills documented by a standardized licensing examination were more successful at obtaining SM for their patients.